2019
DOI: 10.1159/000496740
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Age are Risk Factors of Interval Colon Cancer: A Case-Control Study

Abstract: Background and Aims: Interval colorectal cancer (CRC) is largely related to a poor endoscopic performance or different biology in the development of the polyp. However, patient-related factors were less investigated for their association with interval cancer. We thus evaluated tumor and patient characteristics as predictors of interval cancer in a population from Israel. Methods: In this retrospective study, patients that were diagnosed with colon cancer in our institution and had 2 colonoscopies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
7
0
3
Order By: Relevance
“…This indicates that diabetic patients are at a higher risk of developing colorectal cancer, thus are in higher need for controlled colonoscopy. 16,17 However, these facts may suggest further considerations when assessing diabetic patients with colon cancer in terms of clinical features, treatment, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that diabetic patients are at a higher risk of developing colorectal cancer, thus are in higher need for controlled colonoscopy. 16,17 However, these facts may suggest further considerations when assessing diabetic patients with colon cancer in terms of clinical features, treatment, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…27.7% vs 15.3%, 40.2% vs 26.6%, 25.9% vs 16.1%,14.3% vs 7.8%, respectively; all p < 0.05). Further analysis of colonoscopy characteristics found that the bowel preparation of diagnostic colonoscopy in I-CRAA is better (52.7% vs 23.7%, p < 0.05), the probability of nding a diverticulum is greater (5.4% vs 1.8%, p < 0.05), and the ADR of the diagnostic colonoscopy is higher (29.5% vs 20.9%, p < 0.05) compared with Sp-CRAA.…”
mentioning
confidence: 80%
“…There are su cient evidences to prove that diabetes is an independent risk factor for I-CRC. The study of Laish et al also found that cases with I-CRC had higher prevalence of diabetes [13,14] . Our study reveals the relationship between diabetes, diverticulosis and I-CRAA for the rst time.…”
Section: A Total Of 12622 Patients Underwent 15759 Colonoscopies At Tmentioning
confidence: 90%
“…Many studies have shown that age is associated with the development of CRC ( 35 ). Some studies have found that patients <50 years of age are more likely to have distal CRC, while older patients are more likely to have proximal CRC ( 36 ).…”
Section: Discussionmentioning
confidence: 99%